PENGARUH MANAJEMEN KESISWAAN TERHADAP PRESTASI PESERTA DIDIK DI MTs 16 PERBAUNGAN - Hafis Hasan; Yusuf Hadi Jaya; Inom Nasution (Hijri, 2021)
This study aims to examine the effect of student management on student achievement at MTs 16 Perbaungan. As for the indicators for student management variables include student admissions, student council, and extracurricular, while indicators for student achievement variables include cognitive aspects, affective aspects, and psychomotor aspects. This study uses a quantitative approach using primary data through questionnaires. The results of the tests that have been carried out show that the distribution of scores in the student management variable (X) average class as many as 14 people (17.07%) are below the class average, 4 people (4.88%) are in the class average and as many as 64 people (78.5) above the average. The distribution of Student Achievement variable scores (Y) as many as 20 people (24.39%) are below the interval class average, 6 people (7.32%) are in the interval class average and 54 people (65.8%) are above the average . Shows that the correlation coefficient between the Student Management variable (X) and Student Achievement (Y) is 0.129 with a coefficient of determination (r2) obtained from the calculation results of 0.017 which means that Student Management (X) provides a low relationship of 0.017x 100% = 1.7% of Student Achievement (Y). Based on the analysis conducted above, it is known that the proposed hypothesis is accepted and has been tested empirically. The results of the hypothesis analysis show that there is a very weak and significant influence between Student Management (X) and Student Achievement (Y) of 0.129 with a coefficient of determination (r2) obtained from the calculation results of 0.017 which means that Student Management (X) has an influence very weak at 0.017 x 100% = 1.7% towards Student Achievement (Y). Furthermore, to determine the significance of the influence of the two (Student Management on Student Achievement) it can be seen through the t test". Through the t-test that has been carried out, it turns out that tcount = 3,004 while the value of t table = 2,028. Because tcount (3.004) > ttable (2.048), this indicates that there is a low but significant effect between Student Management variables on Student Achievement in the form of a linear relationship through the regression line = 76.296 + 0.017 X. The equation of this regression line explains that if If the Student Management factor increases by one unit, the Student Achievement will also increase by 76.296 + (0.017) = 10,747 units.Student Achievement